Evaluation of the Department of Planning and Infrastructure’s Bikewest: ‘Bike to work breakfast’ 2004 - McManus, Alexandra; Smith, Jennifer; McManus, Jennifer; McDonald, E. (Sports Medicine Australia, 2005)
The Metropolitan Transport Strategy (1995) proposed moving from a transport system which was dominated by low occupancy car use, to a more balanced transport system of public transport and non-motorised transport options. Creating this change requires initiatives that create critical mass awareness, in work organisations and the community. The ‘Bike to Work Breakfast’ is an example of such an initiative. This year it was held on Friday 12 March, 2004 and aimed to increase awareness of, and promote cycling as an alternative mode of transport to and from work. A free healthy breakfast was provided to everyone who cycled on the day.A total of 1657 participants who attended the 2004 ‘Bike to Work Breakfast’ completed questionnaires. The majority of respondents were male (73%, n=1187). The age of respondents varied, with the most common age group being 31-40 years (28%, n=459) followed by 51 years and over (26%, n=432). Respondents cited a number of different reasons for cycling. The majority indicated improved fitness (88%, n=1460) and enjoyment (71%, n=759) as the main reasons for cycling. Almost half of respondents (44%, n=713) cycled on a daily basis whilst a further 704 (n=43%) participants reported cycling 2-3 times per week. Thirty one percent of respondents (n=509) cycled between 51-100 kilometres per week and 29% (n=480) cycled between one and 50 kilometres per week. The majority of respondents (87%, n=1403) would wear a bicycle helmet when cycling even if they were not compulsory, and ninety five percent (n=1484/1566) of participants who responded supported the use of advance stop lines at key intersections.Over half of respondents (64%, n=1028) reported they would use end of trip cycling facilities if provided in public car parks. Fifty three percent (n= 874) stating they would use secure bike parking, thirty four percent (n=569) would use showers and thirty one percent (n=514) would use lockers if provided. Of the 1657 participants who completed questionnaires, sixty three percent (n=1030) had attended the ‘Bike to Work Breakfast’ previously.